(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Treatment of acute poisoning due to drug overdose in general depends on the prevention of further absorption of the drug and acceleration of elimination, using specific antidotes. Drugs adsorption is of significant importance in physical pharmacy for the preparation of physical antidotes. Objective:To investigate the adsorption of glimepiride from aqueous solution on two adsorbents (activated charcoal and Iraqi kaolin). Method:UV-Spectrophotometric technique was used to obtain the quantitive adsorption data at different conditions of pH and temperature. Results:The quantities of glimepiride adsorbed on activated charcoal and kaolin were increased with decreasing temperature. Adsorption isotherms of glimepiride on both surfaces were consistent with Freundlich adsorption isotherm. Thermodynamic functions (?G, ?H and ?S) were useful in describing the spontaneity of the adsorption process. Conclusion:The quantity of the drug that is adsorbed on activated charcoal was higher than that adsorbed on kaolin surface therefore; the activated charcoal is a better antidote. Keywords: Glimepiride, Adsorption, Activated charcoal, Iraqi kaolin